1990
DOI: 10.1007/bf00216926
|View full text |Cite
|
Sign up to set email alerts
|

High dose folinic acid/etoposide/5-fluorouracil in advanced gastric cancer — a phase II study in elderly patients or patients with cardiac risk

Abstract: Thirty-four consecutive patients with measurable advanced gastric cancer were treated in a disease oriented Phase II study with high-dose folinic acid (HDFA) 300 mg/m2 10 min. inf., followed immediately by etoposide 120 mg/m2 50 min. inf., followed immediately by 5-fluorouracil (5-FU) 500 mg/m2 10 min. inf., given on day 1,2,3 (ELF). Courses were repeated every 22-28 days. All patients who entered this study were older than 65 years or had underlying cardiac disease. Thirty-three patients were evaluable for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 11 publications
2
23
0
1
Order By: Relevance
“…In phase II trials, response rates up to 60% have been reported for regimens such as FAMTX, ELF, EAP, Cisplatin/5-FU or ECF (Klein et al, 1986;Preusser et al, 1989;Wilke et al, 1990;Findley and Cunningham, 1993;Wils, 1996). However, in randomised phase III trials, this high level of activity has only been confirmed for the ECF-regimen (Webb et al, 1997;Waters et al, 1999), whereas for the FAMTX, ELF or cisplatin/5-FU-regimen response rates of 20-25% have been reported (Kelsen et al, 1992;Wilke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In phase II trials, response rates up to 60% have been reported for regimens such as FAMTX, ELF, EAP, Cisplatin/5-FU or ECF (Klein et al, 1986;Preusser et al, 1989;Wilke et al, 1990;Findley and Cunningham, 1993;Wils, 1996). However, in randomised phase III trials, this high level of activity has only been confirmed for the ECF-regimen (Webb et al, 1997;Waters et al, 1999), whereas for the FAMTX, ELF or cisplatin/5-FU-regimen response rates of 20-25% have been reported (Kelsen et al, 1992;Wilke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is used primarily for palliation of symptoms (Findlay and Cunningham, 1993;Wils, 1996;De Vivo et al, 2000). In the past three decades, a variety of chemotherapy regimens were developed for the treatment of advanced gastric cancer (MacDonald et al, 1980;Preusser et al, 1989;Wilke et al, 1990;Wils et al, 1991;Kim et al, 1993;Cocconi et al, 1994;Zaniboni et al, 1995;Ychou et al, 1996;Cheng et al, 1998). All these regimens had variable degrees of success in phase II trials; however, results of the subsequent phase III trials often failed to confirm the relatively high response rates of earlier reports (Kelsen et al, 1992;Kim et al, 1993;Cocconi et al, 1994;Webb et al, 1997;Vanhoefer et al, 2000).…”
mentioning
confidence: 99%
“…To the best of our knowledge, six phase II studies have been published in international peer-reviewed journals between 1990 and 2002 (Wilke et al, 1990;Cascinu et al, 1994;Cascinu and Catalano, 1995;Di Bartolomeo et al, 1995;Hartung et al, 2000;Ikeda et al, 2002). In five of these trials, chemotherapy consisted of leucovorin-modulated 5-fluorouracil in combination with cisplatin, epi-doxorubicin, etoposide or mitomycin-C. A phase II study investigated the toxicity profile and the activity of single-agent doxifluridine (Ikeda et al, 2002).…”
Section: Discussionmentioning
confidence: 99%